Modalitas Terbaru Pengobatan Luka Bakar - Hafiz Khairun Marwan; Andi Irwansyah Achmad; Nurul Rumila Roem (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Burn injuries are complex tissue damage often accompanied by serious complications such as infection, systemic inflammation, and organ dysfunction. Effective burn management requires a comprehensive multidisciplinary approach, including infection control, local wound care, nutritional support, and regenerative therapy. Along with advances in science and technology, various novel treatment modalities have been developed to accelerate healing, reduce scarring, and improve patients’ quality of life. This study aims to evaluate the effectiveness and clinical prospects of the latest burn treatment modalities through a review of relevant literature from 2021 to 2025. This research employed a descriptive qualitative literature review method, analyzing 10 relevant scientific articles obtained from academic databases such as PubMed, ScienceDirect, and Google Scholar. The reviewed modalities include stem cell therapy, Platelet Rich Plasma (PRP), silver nanoparticles, nanofiber and hydrogel-based dressings, natural extracts such as aloe vera and binahong, as well as advanced technologies like smart dressings and low-level laser therapy. The results indicate that regenerative and smart technology-based approaches significantly enhance epithelialization, reduce infection, and improve tissue repair. Natural therapies also show promising potential as safe, affordable, and effective treatment alternatives. In conclusion, the integration of biological therapy, phytotherapy, and modern technology represents a promising direction in contemporary burn care. Further large-scale clinical research is needed to confirm the long-term safety and effectiveness of each modality.